Optimizing Canva Utilization to Enhance Students’ Visual Creativity at Tuah Negeri Islamic Institute - Rahma Darini; Yera Putri Rahayu; Putri Diyah Makarti Desi; Habib Ullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study analyzes the effect of using the graphic design application Canva on the visual creativity of students at the Institut Keislaman Tuah Negeri. Employing a quantitative approach with a descriptive correlational design, a total of 73 students participated through an online questionnaire. Reliability testing indicated that the visual creativity scale achieved a Cronbach’s alpha of 0.81, while the Canva usage scale obtained a value of 0.48. Pearson correlation analysis revealed a positive and significant relationship between Canva usage and visual creativity (r = 0.50; p < 0.001). Simple linear regression produced the equation Y = 2.58 + 0.43X with an R² value of 0.25, indicating that 24.8% of the variance in visual creativity was explained by the use of Canva. These findings confirm that Canva can serve as an effective visual learning medium for enhancing students’ creativity. This study recommends increased institutional support and technology training to optimize the use of Canva in educational settings.